Security Management As A Form Of Social Control Against Crime In The UIR Campus Environment - Madani, Raudho; Novarizal, Riky; Zulherawan, M. (Doctoral Program of Social Science Pasundan University, 2025)
Security in the campus environment is a fundamental aspect in creating a safe and conducive academic atmosphere. Riau Islamic University (UIR) as one of the higher education institutions has the responsibility to implement a security system to prevent and overcome various forms of crime that can occur in the campus environment. Crime on campus, such as vehicle theft, fights, and harassment, can have a negative impact on the comfort of students and academics. Therefore, security management plays a role as a form of social control that aims to maintain order and reduce crime rates in the campus environment. This study aims to analyze the role of security management in preventing and handling crime on the UIR campus and to identify the obstacles faced in implementing the security system. The method used in this study is qualitative with a descriptive approach. Data were collected through in-depth interviews with security officers, students, lecturers, and the community around the campus, as well as direct observation of the security system implemented. The results of the study indicate that UIR has implemented various security strategies, such as routine patrols, installation of CCTV at strategic points, and enforcement of rules for students and campus visitors. However, there are still some obstacles, such as the limited number of security personnel, lack of student awareness of security, and the need for increased coordination between the campus and the surrounding community in maintaining security. Therefore, this study recommends increasing the number of security personnel, optimizing surveillance technology, and strengthening cooperation with law enforcement officers to improve the effectiveness of social control over crime in the UIR campus environment.